Risk mapping of Chlorine gas dispersion from a storage plant in a dense urban area of Lahore - Rafaqat Warda,; Muhammad M. Shafique,; Gill Kaif,; Ashraf Nasir,; Chuanli Huang,; Shabbir Salman,; Aqeel Suliman,; Weiguo Song, (Technium Social Sciences Journal, 2021)
In recent times, with the increasing population in urban areas, the adverse events happening due to explosion and dispersion of toxic chemicals has increased. Events like toxic gas dispersion can cause severe environmental issues that endanger human safety and health. Consequence hazard modeling and vulnerable population assessment are critical to predict and minimize the losses. Chlorine is not only utilized in water treatment plants as a disinfectant, but it ca n also lead to some serious concerns to human health. In this paper, the modeling of chlorine release has been investigated for chlorine storage plant by using Heavy gas dispersion model. The modeling results showed that the cloud of chlorine is about 1.9 miles across just downwind of the release for accidental release of chlorine in the summer; however, the probability of fatality is 100 % in a whole year in a distance of 0.36 miles from the Storage Place. As a significant result, the land around the chlorination unit covering a range of approximately 1.9 miles is vulnerable in all wind directions and in the case of South-West direction of the wind, vulnerable population is highly dense, risk prevention in that region should be accounted for. Affected Population and areas at risk are calculated, which illustrates the toxically impacted areas and the population in need of immediate help and evacuation. Such studies can serve as a useful tool for decision-makers to prepare an emergency plan in case of accidental releases.